Statin-associated necrotizing myopathy: a rare etiology - Moita,Catarina Ferreira (2020)
Abstract Introduction: Necrotizing autoimmune myopathy is a rare entity characterized by proximal muscle weakness, elevated creatine kinase levels, potential autoantibody presence, and myofiber necrosis with reduced or absent inflammation. Case description: We report the case of a 72-year-old female with a 3-week-history of asthenia, increasing proximal tetraparesis, without pain, fever, or other symptoms, and elevated creatine kinase levels. Previous history was remarkable for dyslipidemia controlled with statin therapy. A muscular biopsy was performed, leading to the diagnosis of necrotizing myopathy. A body computed tomography (CT) scan was normal. Corticotherapy was initiated with progressive clinical and analytical improvement. Discussion: This case depicts an uncommon and underdiagnosed pathology which may be associated with statin treatment or cancer, that requires an early diagnosis and close follow-up for better clinical outcomes.